Experimental validation of a Nonlinear Model based Control scheme on the Variable area tank process. Issue 1 (2016) - Arasu, S. Kapil; Panda, Atanu; Prakash, J.
Abstract: In this paper, the authors have proposed a simple non-linear model based control scheme for the variable area tank process. The proposed control scheme relies on the nonlinear model of the conical tank process. The parameters of the nonlinear model have been determined using empirical approach. The proposed control algorithm has been implemented on pilot scale conical tank experimental setup. The performance of the proposed control scheme is compared with that of a gain scheduled PI controller.